Postgraduate training of Mathematics teachers of higher education in Holguin - Escalona Reyes, Miguel (2022)
The permanent improvement of professionals in Cuba is a priority of Higher Education, universities make countless efforts to guarantee it in all its areas; In the case of mathematics teachers, this is essential, because in addition to the difficulties in learning its contents, there is a great variety in the training of the teachers who teach it. The master's degree in University Mathematical Education, which is developed at the University of Holguín, tries to address this situation from the permanent training of professionals who work as teachers of this discipline in Higher Education. In this article, some of the experiences and results obtained in this program are disclosed, as well as its impact on the territory of Holguin.